An integrated approach for performance measurement of Indian telecom service providers. (2019) - Kumar, Pravin; Sharma, Garima
The purpose of this research paper is to measure the operational performance of cellular mobile telephone service providers (CMTSP) in India. In this paper, analytic hierarchy process (AHP) and preference ranking organisation method for enrichment evaluation (PROMETHEE) integrated approach are used to compare the operational performances of CMTSP. This analysis is based on the information gathered by the Telecom Regulatory Authority of India, for the duration of January-March 2016. Three major parameters covering eight criteria: network availability, connection accessibility, and connection retainability are incorporated in this analysis. On the basis of the analysis, it has been observed that Reliance Communication has the first ranking and MTNL has the last ranking. This paper may help the management in the creation of a plan of action to improve the performance of the company by benchmarking the operational parameters on the basis of this model.